PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PERUSAHAAN - Puspita, Irana Kartika; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Profitability is the net profit from a number companyâs of policies and decisions. The profitability ratio measures the ability of the company to gain profitin relation with sales, total assets, and even own capital. Profitability of a company is measured by the success of the company and the ability of the capital within a company, by comparing the profit and the capital which has been employed in operations. In the use of this debt, the need for caution over the risk resulting from the use of debt. This is due to the use of debt has a high risk that the cost of capital. Therefore, the decision to use debt, the company must pay attention to the balance between equity and outside capital to be used. If the capital structure has been under optimal capital structure targets, then each additional indebtedness would increase the value of the company. The result of the research shows that research model is fit or feasible. The independent variables have positive influence to the profitability. The Corporate Social Responsibility (CSR) and the Capital Structure (SM) is the variable which has positive influence to the profitability which means that the ability of the company in generating profit is done by performing CSR and Capital Structure.Keywords: Corporate Social Responsibility, Capital Structure, Profitability, DAR, ROE